Metabolomics analysis of type 2 diabetes remission identifies 12 metabolites with predictive capacity: a CORDIOPREV clinical trial study. - Mora-Ortiz, Marina.; Alcala-Diaz, Juan F.; Rangel-Zuñiga, Oriol Alberto.; Arenas-de Larriva, Antonio Pablo.; Abollo-Jimenez, Fernando.; Luque-Cordoba, Diego.; Priego-Capote, Feliciano.; Malagon, Maria M.; Delgado-Lista, Javier.; Ordovas, Jose M.; Perez-Martinez, Pablo.; Camargo, Antonio.; Lopez-Miranda, Jose. (Tufts University. Tisch Library., 2022)
Keywords: Diabetes, Insulin resistance, Prospective human study, Metabolomics.; Springer Open.